BizTalk 2013 Recipes A Problem-Solution Approach - Beckner, Mark.; Dharanikota, Kishore; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
BizTalk 2013 Recipes provides ready-made solutions to BizTalk Server 2013 developers. The recipes in the book save you the effort of developing your own solutions to common problems that have been solved many times over. The solutions demonstrate sound practice, the result of hard-earned wisdom by those who have gone before. Presented in a step-by-step format with clear code examples and explanations, the solutions in BizTalk 2013 Recipes help you take advantage of new features and deeper capabilities in BizTalk Server 2013. You$1 (Bll learn to integrate your solutions with the cloud, configure BizTalk on Azure, work with electronic data interchange (EDI), and deploy the growing range of adapters for integrating with the different systems and technologies that you will encounter. You$1 (Bll find recipes covering all the core areas: schemas, maps, orchestrations, messaging and more. BizTalk Server 2013 is Microsoft$1 (Bs market-leading platform for orchestrating process flow across disparate applications. BizTalk 2013 Recipes is your key to unlocking the full power of that platform.s
Keywords: Computer science; Computer Science; Computer Science, general; e-Commerce/e-business.